SYNTHESIS HIGH SILICA CHABAZITE ZEOLITE WITHOUT ORGANIC COMPOUNDS - Rahmi Kadir, Iftitah
Chabazite (CHA) type zeolite is a microporous material with 8 channel rings that has great potential to be applied as a catalyst in MTO (Methanol to Olefins) reaction. Generally high silica CHA with high levels of high silica is hydrophobic and synthesized using the help of organic compounds N,N,N-Trimethyl-1- adamanammonium hydroxide (TMAdaOH) as a structure directing Agent (SDA). However, the use of natural resources, especially TMAdaOH is very costly and is not environmentally friendly. To open the pores of the zeolite, this organic compound must be removed by high temperature combustion. In the early stages of this research, CHA was synthesized through FAU to CHA interzeolite transformation. However the products has low silica content (Si/Al mole ratio = 2). Therefore we designed new synthesis route of CHA without SDA by reacting the products of inter-transformation process with additional silica and alumina precursors, NaOH, and KOH. Hydrothermal treatment is then applied to this mixture at 170 oC for 24 hours. Various molar composition of Na2O and K2O (0.1 to 0.4) was conducted to study the synergistic effect of Na+ and K+ to the crystallization of CHA with high Si/Al ratio. X-ray diffraction (XRD) analysis showed that CHA-type zeolite can be regenerated and X-ray fluorescence (XRF) measurement showed that Si/Al ratio of = 4 was produced by applying two molar composition of Na2O and K2O respectively 0.3 and 0.1. Scanning Electron Microscope (SEM) images of the product showed similar morphology and particle size to those of inter-transformation CHA crystal.